PERANAN PASAR TRADISIONAL DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT (STUDI KASUS PADA PASAR PA’BAENG-BAENG DI KECAMATAN TAMALATE KOTA MAKASSAR) - Ikram, Muhammad; Nur, Miftahul Jannah (Jurnal Ekonomi Balance, 2012)
This study aims to determine how the government plays a role in accommodating the development of the Pa'baeng-baeng traditional market in the Tamalate sub-district of Makassar City as well as the function of traditional markets in the welfare of the community. This study uses a qualitative descriptive approach. Data analysis is done qualitatively through data reduction in accordance with the main points in the research focus and converging on the main issues that will be answered in this study. The results of this study indicate that the role of traditional markets in improving community welfare has been successful, although it has not been optimal, this is evident from the many people who rely on this traditional market with sufficient income to meet their basic needs and expenses so that they can meet their needs. The government's attention to market management still needs to be improved, especially the expansion of vehicle parking spaces and reducing traders' complaints about daily market retribution which is considered quite high.